(untitled) (Interdisciplinary Studies Journal, 2024)
This article presents the project "Human Rights and Teacher Training" from PET - Pedagogy at UNIPAMPA - Campus Jaguarão, carried out in the second semester of 2021. The project addresses the relevance of Human Rights in teacher training, utilizing university extension as a means of incorporating the theme. With a structured schedule, the discussion focused on the critical conceptualization of Human Rights in teacher training. Recognizing gaps in teacher education curricula, the project aimed to fill these shortcomings, emphasizing the crucial role of university extension in knowledge construction. The conception of Human Rights as essential to human dignity was explored, emphasizing the university’s role in this context. By addressing the theme in teacher education programs, the project stimulated awareness of rights and understanding of the daily struggle for the desired freedom. Teacher training was recognized as a strategy in this fight, connecting theory to practice to facilitate understanding and emphasize the importance of Human Rights. University extension was highlighted as a means to promote dialogical interactions in teacher training. Aligned with the National Policy for University Extension, the project aimed to complement the education of future teachers and educators in Basic Education, solidifying the relationship between theory and practice in Human Rights.